Functional Diversity of Human Basic Helix-Loop-Helix Transcription Factor TCF4 Isoforms Generated by Alternative 5′ Exon Usage and Splicing - Sepp, Mari (Public Library of Science, 2011)
BACKGROUND: Transcription factor 4 (TCF4 alias ITF2, E2-2, ME2 or SEF2) is a ubiquitous class A basic helix-loop-helix protein that binds to E-box DNA sequences (CANNTG). While involved in the development and functioning of many different cell types, recent studies point to important roles for TCF4 in the nervous system. Specifically, human TCF4 gene is implicated in susceptibility to schizophrenia and TCF4 haploinsufficiency is the cause of the Pitt-Hopkins mental retardation syndrome. However, the structure, expression and coding potential of the human TCF4 gene have not been described in detail. PRINCIPAL FINDINGS: In the present study we used human tissue samples to characterize human TCF4 gene structure and TCF4 expression at mRNA and protein level. We report that although widely expressed, human TCF4 mRNA expression is particularly high in the brain. We demonstrate that usage of numerous 5′ exons of the human TCF4 gene potentially yields in TCF4 protein isoforms with 18 different N-termini. In addition, the diversity of isoforms is increased by alternative splicing of several internal exons. For functional characterization of TCF4 isoforms, we overexpressed individual isoforms in cultured human cells. Our analysis revealed that subcellular distribution of TCF4 isoforms is differentially regulated: Some isoforms contain a bipartite nuclear localization signal and are exclusively nuclear, whereas distribution of other isoforms relies on heterodimerization partners. Furthermore, the ability of different TCF4 isoforms to regulate E-box controlled reporter gene transcription is varied depending on whether one or both of the two TCF4 transcription activation domains are present in the protein. Both TCF4 activation domains are able to activate transcription independently, but act synergistically in combination. CONCLUSIONS: Altogether, in this study we have described the inter-tissue variability of TCF4 expression in human and provided evidence about the functional diversity of the alternative TCF4 protein isoforms.